Projeto ótimo de múltiplos sistemas passivos de absorção distribuídos espacialmente - Costa, Mariana Miglio Americano da (2019)
Tuned-Mass-Dampers (TMD) have been widely used to suppress undesirable structural vibrations. Nevertheless, the performance of TMDs designs is quite sensitive to uncertainties associated to the model tuning and physical system construction. This thesis proposes (i) a methodology that seeks optimum designs of Multiple TMDs spatially distributed and (ii) a straightforward way to analyze the level of robustness of the optimum design under different levels of model uncertainties. These analyzes were performed in a beam and a rectangular plate aiming at understanding the characteristics of the approach and its effectiveness. The optimum solution is determined by means of an optimization algorithm and the robustness is computed by means of Monte Carlo simulation analyses. The analyses consider that uncertainties may come from TMD model parameters, from the main system parameters and from both of them simultaneously. These analyses allow one to build a design chart from which one may obtain the robustness of the optimum solution as a function of model uncertainties.